A arquitetura política e cultural do tempo histórico na modernização de Belo Horizonte (1940-1945) - Denise Marques Bahia (2011)
The subject matter of this thesis is the political and cultural construction of historical time in the process of modernization of Belo Horizonte, from 1940-1945. The work investigates the political and socio-historical conditions, both at the local and national levels, of the constructive process of the notions of identity, memory and cultural heritage, and of the consolidation of the Brazilian modern architecture (1917-1945). It departs from the critical and interpretative analysis of two contemporaneous events which were significant to the citys experience: the conception of the Pampulha Architectural Complex and of the Historical Museum of Belo Horizonte, under the municipal government office of Juscelino Kubitschek. According to the modernist ideas, a cultural movement from the 1920s, the Ministry of Education in Rio de Janeiro (1936-1943), one of the inaugural landmarks of the Brazilian modern architecture, and the SPHAN, National Artistic Historical Heritage Service, in 1937, during the Estado Novo, were established as well the simultaneous creation and construction and of Pampulha (1942-1943) and the Historical Museum, in Belo Horizonte (1941-1943). These political actions suggest a common strategy of working with a dual temporality within a project of modernization at the local and national levels, which calls for a critical examination. In the case of Belo Horizonte, within the developmentist political project undertaken by Kubitschek, there is, at the one hand, the construction of the future, expanding the city towards its north side, and creating a complex of tourism and leisure, with a new architectural repertoire created by Oscar Niemeyer to express such modernity and, on the other hand, the construction of the past, through the conception of a place in the urban memory, based in a old mansion from Curral Del Rei, the village which has become the new republican capital planned in the end of the XIX century. Such dual temporality allows us to define the time of modernization of Belo Horizonte as historical time to the extent that the temporal dimension of the past engages in a continuous relation of reciprocity with the temporal dimension of the future. In this perspective, we investigate the architecture of Pampulha and the creation of the Historical Museum as social and political construction and as forms of expression which ultimately give visibility to the historical time. The modernization of the city is analysed with regard to its affinities and tensions with the process of formation of the nation and of State, during the office of the late president Getúlio Vargas. Hence, the thesis assesses, in that period, the relationship between the State and the main actors of the architectural field to shed light on the understanding of the political and cultural construction of time and the meaning in terms of identity and history of the architecture and the heritage institutions in the modernization of Belo Horizonte in the 1940s.